2007
DOI: 10.1111/j.1557-9263.2006.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal diets of insectivorous birds using canopy gaps in a bottomland forest

Abstract: Little is known about how insectivorous bird diets are influenced by arthropod availability and about how these relationships vary seasonally. We captured birds in forest-canopy gaps and adjacent mature forest during 2001 and 2002 at the Savannah River Site in Barnwell County, South Carolina, and flushed their crops to gather information about arthropods eaten during four periods: spring migration, breeding, postbreeding, and fall migration. Arthropod availability for foliage-and ground-gleaning birds was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
3
21
0
1
Order By: Relevance
“…Our study suggests that this may be due to higher food abundance as percent shade decreases in gaps. Our findings support one alternative hypothesis put forth by Moorman et al (2007): that increased bird use of canopy gaps is due to increased food abundance. However, Greenberg and Forrest (2003) found that abundance of most arthropod taxa measured (including Carabidae and Araneae) was lower in canopy gaps compared to control forest plots.…”
Section: Stand and Microhabitat Level Patternssupporting
confidence: 84%
“…Our study suggests that this may be due to higher food abundance as percent shade decreases in gaps. Our findings support one alternative hypothesis put forth by Moorman et al (2007): that increased bird use of canopy gaps is due to increased food abundance. However, Greenberg and Forrest (2003) found that abundance of most arthropod taxa measured (including Carabidae and Araneae) was lower in canopy gaps compared to control forest plots.…”
Section: Stand and Microhabitat Level Patternssupporting
confidence: 84%
“…These three species were predominantly found in agricultural lands and the above insect prey formed principal food items due to their greater availability. Moorman et al (2007) reported that Coleopterans and Hemipterans formed the major diet of foliage-gleaning and ground-gleaning insectivorous birds. Many other investigators also have determined Coleopterans, Hemipterans and Hymenopterans (Mason & Maxwell-Lefroy 1912;Sodhi 1986;Kaspari & Joern 1993;Parasharya et al 1994;Sivakumaran & Thiyagesan 2003;Yard et al 2004;Asokan et al 2008) as primary food resource of insectivorous birds.…”
Section: Resultsmentioning
confidence: 99%
“…Prey vary in nutritional value (Robel et al 1995;Arnold et al 2010;Razeng & Watson 2015) and this may influence birds to preferentially target certain taxa (Razeng & Watson 2015). Additionally, birds employ specific strategies, such as foraging in a certain strata, using particular capture methods, or feeding at a certain time of day (Higgins & Peter 2002;Antos & Bennett 2006;Moorman et al 2007) and invertebrate sampling methods need to take these into consideration. Thus, it is unclear whether it is appropriate to treat all prey equally in food availability studies and greater understanding of the issue may be derived by taking some of these factors into consideration.…”
Section: Effects Of Limited Resource Availability In Highly-modified mentioning
confidence: 99%
“…Instead of basing this investigation on total invertebrate density as is often done (Burke & Nol 1998;Zanette et al 2000), I only consider prey taxa known to be consumed by robins. Drawing inferences based on total invertebrate density may be misleading given that birds show preferences towards certain prey groups (Naef-Daenzer et al 2000;Hagar et al 2007;Moorman et al 2007;Razeng & Watson 2012 Maron et al (2012) and what these changes might mean for the population.…”
Section: Thesis Outlinementioning
confidence: 99%
See 1 more Smart Citation